2017
DOI: 10.3390/ijms18112151
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Beads-Based Sensor with Tailored Sensitivity for Rapid and Single-Step Amperometric Determination of miRNAs

Abstract: This work describes a sensitive amperometric magneto-biosensor for single-step and rapid determination of microRNAs (miRNAs). The developed strategy involves the use of direct hybridization of the target miRNA (miRNA-21) with a specific biotinylated DNA probe immobilized on streptavidin-modified magnetic beads (MBs), and labeling of the resulting heteroduplexes with a specific DNA–RNA antibody and the bacterial protein A (ProtA) conjugated with an horseradish peroxidase (HRP) homopolymer (Poly-HRP40) as an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…The achieved LOD is similar (0.2 versus 0.4 nM) [ 27 ] or higher than those reported for other MBs-based approaches for the determination of miRNAs (6 aM [ 28 ], 0.4 pM [ 31 ], 2.4 pM [ 29 ], 40 pM [ 26 ], and 60 pM [ 32 ]). However, the methodology reported here is carried out in a single incubation step (once the MBs were modified with the b-Cp) with a very low concentration of synthetic nucleic acid probe (2.5 nM) and without any amplification strategy.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The achieved LOD is similar (0.2 versus 0.4 nM) [ 27 ] or higher than those reported for other MBs-based approaches for the determination of miRNAs (6 aM [ 28 ], 0.4 pM [ 31 ], 2.4 pM [ 29 ], 40 pM [ 26 ], and 60 pM [ 32 ]). However, the methodology reported here is carried out in a single incubation step (once the MBs were modified with the b-Cp) with a very low concentration of synthetic nucleic acid probe (2.5 nM) and without any amplification strategy.…”
Section: Resultssupporting
confidence: 64%
“…These advantages have been coupled in many cases with those provided by planar disposable electrodes (versatility of fabrication and mass production at low cost) to develop different competitive electrochemical biosensing platforms for the quantification of miRNAs. Nevertheless, most of these platforms involve different preparation steps and require the use of expensive affinity reagents [ 26 , 27 , 28 , 29 , 30 , 31 ] and multiple probes in connection with amplification strategies [ 28 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This robust electrochemical biosensing strategy was also demonstrated through high-sensitivity,r apid, simultaneous detection of miRNAs directly from metastatic cancer cells and human tumor tissues with ap ico-molar sensitivity. [29] Similar sandwich setup based on magnetic separation and enzyme labeling was demonstrated by the detection of exosomes,i ndicating the versatility of this strategy. [30] Furthermore,b uilding on the same design logic involving the nucleic acid hybridization and amplification system, ac omparison study demonstrated 11 different methods for nucleic acid detection, confirming the diversity and generality of this electrochemical sensing strategy for high-sensitivity nucleic acid detection.…”
Section: Immunomagnetic Beads With Selected Hybridizationmentioning
confidence: 85%
“…With the aim of overcoming some of these limitations, attractive EC biosensors have recently been proposed for the determination of miRNAs using novel bioreceptors such as tombusvirus protein p19, with a high affinity for the determination of RNA‐RNA homohybrids of limited length or commercial antibodies with a high affinity for RNA‐DNA heteroduplexes of any length . Moreover, to minimize the disadvantages of conventional amplification strategies, the use of an isothermal amplification known as hybridization chain reaction (HCR) has recently been proposed for the determination of miRNAs .…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of new strategies with improved sensitivity while maintaining the simplicity and assays time would be tremendously relevant for the determination of other miRNAs with fewer copies or in more challenging clinical samples which require higher sensitivity. It is also important to note that the strategies developed so far have only been applied to the individual or simultaneous detection of two target miRNAs .…”
Section: Introductionmentioning
confidence: 99%